aoNo Good Story To Tella-Informal Settlements Still As Big As 1994. A Case of Midvaal Municipality in Sedibeng District (Global Journal of Human-Social Science, 2014)
The apartheid regime kept the black majority in the informal settlements where they endured the most agonizing brunt of urban underdevelopment. Democratic government of South Africa today continues to shape, reshape and reinforce this underdevelopment albeit in new forms. This paper examines the vulnerability of residents of informal settlement in Midvaal Municipality pursued through a case study of Sicelo Shiceka, an informal settlement. The empirical findings of this study unpacked that informal settlements are largely vulnerable to lack of water, ablation, HIV/AIDS, crime and violence, xenophobia and unemployment amongst others. In response to some the vulnerabilities such as lack of income, informal residents have adopted a range of livelihood strategies including commercialization of sex, domestic work and so on. The study concludes that the vulnerability and lived experiences of residents points to poverty. These findings are projected through in-depth interviews which are a technique of qualitative methodology. Theoratically, the paper is informed by the social sustainability and sustainable livelihood approach.
Keywords: informal; informal settlements; sustainability; livelihood; vulnerability